2019
DOI: 10.1021/acs.orglett.9b00761
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Construction of Fused Heteropolycyclic Aromatics via Palladium-Catalyzed Domino Arylations of Imidazopyridine Derivatives

Abstract: By using diaryliodonium salts, a novel approach of a palladium-catalyzed cascade of diarylation/intramolecular dehydrogenative coupling reaction has been developed in the synthesis of phenanthro-imidazopyridine fused heteropolycycles. The method can tolerate various substrates, and the target products were rapidly constructed in one pot. Furthermore, studies of the detailed reaction mechanism provide an insight into the C−H functionalization of 2-aryl-imidazopyridine derivatives and the C−C bond formations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Several advantages such as reduction of the synthetic steps and no production of stoichiometric amount of toxic by-products are provided by using domino arylations of imidazopyridine derivatives. In this context, a palladium-catalyzed direct arylation of 2-phenylimidazo[1-α]pyridine using diphenyliodonium triflate as a coupling partner was described by Wang et al [89]. The screening of the reaction conditions revealed that using K 2 CO 3 as the base and Pd(OAc) 2 (10 mol%) as a catalyst in DMF at 100 • C for 24 h led to the selective C3-phenylation in 91% (Scheme 18).…”
Section: Introductionmentioning
confidence: 99%
“…Several advantages such as reduction of the synthetic steps and no production of stoichiometric amount of toxic by-products are provided by using domino arylations of imidazopyridine derivatives. In this context, a palladium-catalyzed direct arylation of 2-phenylimidazo[1-α]pyridine using diphenyliodonium triflate as a coupling partner was described by Wang et al [89]. The screening of the reaction conditions revealed that using K 2 CO 3 as the base and Pd(OAc) 2 (10 mol%) as a catalyst in DMF at 100 • C for 24 h led to the selective C3-phenylation in 91% (Scheme 18).…”
Section: Introductionmentioning
confidence: 99%
“…All the starting materials and reagents for the synthesis were obtained from commercial suppliers and directly used without further purification. First, compounds IP‐Br, 1 , and 2 were prepared as reported . A one‐step Suzuki palladium‐catalyzed cross‐coupling reaction was used to synthesize the target products IP‐PPI and IP‐DPPI.…”
Section: Resultsmentioning
confidence: 99%
“…First, compoundsI P-Br, 1,a nd 2 were prepared as reported. [19,30] Ao ne-step Suzuki palladium-catalyzedc ross-coupling reactionw as used to synthesize the target products IP-PPI and IP-DPPI. The crude product was purified by silica column chromatography and characterizedw ith 1 HNMR spectroscopy, mass spectrometry,and elemental analysis.…”
Section: Synthesismentioning
confidence: 99%
“…Diarylation and subsequent intramolecular cyclization of 2‐phenylimidazo[1, 2‐ a ]pyridine derivatives with diaryliodonium salts was reported by Xue and his co‐workers in 2019 (Scheme 24). [50] One important observation of this methodology is that except acetic acid no other solvents result in the desired product. The reaction proceeds smoothly for electronically varied 2‐phenylimidazo[1, 2‐ a ]pyridine scaffolds.…”
Section: Functionalization Reactions Of Imidazo[1 2‐a]pyridinementioning
confidence: 99%